Constraining Decadal Variability Yields Skillful Projections of Near‐Term Climate Change - Mahmood, Rashed; Donat, Markus G.; Ortega, Pablo; Doblas‐Reyes, Francisco J.; Ruprich‐Robert, Yohan (Geophysical research letters, 2021)
Targeted adaptation to near‐term climate change requires accurate, reliable, and actionable climate information for the next few decades. Climate projections simulate the response to radiative forcing, but are subject to substantial uncertainties due to internal variability. Decadal climate predictions aim to reduce this uncertainty by initializing the simulations using observations, but are typically limited to the next 10 years. Here, we use decadal predictions to constrain climate projections beyond the next decade and demonstrate that accounting for climate variability improves regional projections of 20‐year average temperatures. Applying this constraint to climate projections of the near future until 2035, summer temperatures over land regions in Asia and Africa tend to show stronger changes within the warming range simulated by the larger, unconstrained, ensemble—consistent with a warm phase in North Atlantic variability. This improved regional climate information can enable tailored adaptation to climate changes in the coming decades. Plain Language Summary We present a novel approach to reduce the uncertainty from internal variability, which can limit the capability to develop suitable adaptation strategies, in climate projections of the near future. This approach combines information from decadal climate predictions and climate projections to constrain decadal climate variability. We demonstrate that this constraint improves the skill of temperature projections for the next 20 years after starting the prediction. Applying this method to predict the near‐term future until 2035, we find an increased probability of stronger warming during summer in several land regions, consistent with a warm phase in North Atlantic variability. Such improved estimates of near‐term climate change are a promising basis for developing better adaptation strategies and avoiding mal‐adaptation. Key Points We present a novel approach to reduce the uncertainty and improve the accuracy of near‐term climate projections The method merges decadal predictions with climate projections, constraining the decadal variability in the projections This approach increases the skill of regional temperature projections for the next 20 years